PERAN MASJID KAMPUS INSTITUT AGAMA ISLAM NEGERI (IAIN) PALU - Jihan Jihan (ISTIQRA, 2016)
This study discusses the campus mosque's role in the development of students` activities. Related to the development of students` activities, campus mosque of IAIN Palu has a role and a huge potential. It is obvious from the student activity every day to make the mosque as a place of study, discussion, and training for the students` agencies. Among the students` activities are the recitation of the Qur`an, reviewing the book, learning recitations, as well as regular activities undertaken Campus da`wah institution of IAIN Palu. The role of the campus mosque was also strongly felt by students and alumni who served as a manager or ta'mir mosque. They nurtured and empowered to be able to preach in addition also skilled in managing/manage the mosque well. Campus mosque of IAIN Palu also plays a role in community development. Among the basic recitation held for children around the mosque through Qur`an recitation area held each evening between Maghrib and Isha. It also held lectures for adults and parents.Optimizing the campus mosque carried out by organizing various events and activities both educational, cultural, and economic. Optimizing the role and function of the mosque is very beneficial for students` development in particular and society in general, not only in the aspect of ritual worship activities, but also for the coaching aspect of religious, social, and economic